Private property, capital and the state in the development of white commercial farming in South Africa, 1910-1986 - De Jager, B (Department of Historical Studies, 2018)
This dissertation examines the value of state assistance for small farmers in countries beset by capital deficits. It explores how undercapitalisation inhibited capitalist development of white commercial agriculture in South Africa between 1910 and 1936. From 1937, South Africa's nationalist government intervened in markets through marketing control boards to resolve capital constraints. Accumulation, liberal credit provision and investment followed. Between 1973 and 1981 state control over markets diminished. Nonetheless development continued. This thesis calls into contention the New Institutional Economic school's premise that state involvement should be limited to protecting institutions that optimise the free market. In their approach, protection of private property is the only path to sustainable economic development. The history of white agriculture in South Africa from 1910 demonstrates that state intervention that resolves capital deficits in the context of a competitive market economy is another sustainable path.